Le féminisme décolonial en Abya Yala - Curiel, Ochy; De Roo, Priscilla (Multitudes, 2021)
Les rapports sociaux de race, de genre, de sexe sont inextricablement mêlés : telle est une idée centrale du féminisme décolonial tel qu’il se déploie depuis Abya Yala, du nom que le peuple kuna donnait au continent américain. L’article situe l’importance de renommer les femmes et féministes d’origine autochtone, une manière de défaire les discours coloniaux (parfois tenus par des universitaires féministes) sur les pratiques de genre avant la colonialité/modernité. Ochy Curiel illustre cette idée à partir de l’expérience du GLEFAS (Groupe latino-américain de formation et d’action féministe) : le décolonial n’y est pas seulement une critique du savoir académique, il est profondément ancré dans des pratiques autogestionnaires de luttes anticapitalistes, dans le lesbianisme politique, dans la rue, dans les associations, dans les organisations communautaires.
Keywords: amériques; anthropologie; anthropologie sociale; approches et analyses; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; intersectionnalité; lesbianisme; militance; pol4212; premier cycle; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis